Posterior Fossa Epithelial Cyst: Case Reportand Review of the Literature - Elmadbouh, Hani; Halpin, Shawn F. S.; Neal, Jim; Hatfield, Richard H.; Hourihan, Margaret D. (American Journal of Neuroradiology, 1999)
Summary: A 49-year old woman with progressive cranial nerve signs and hemiparesis was found at MR imaging and at surgery to have a cyst at the foramen magnum. Immunohistochemistry and electron microscopy showed an epithelial cyst of endodermal origin. MR findings were of an extraaxial mass, with short T1 and T2 times. Unless immunohistochemistry and electron microscopy are used in the final diagnosis of such cysts, all posterior fossa cysts lined by a single layer of epithelium should be described simply as epithelial cysts.